A study on the association of student learning style and the performance of the first year and fourth year pharmacy students at UiTM Puncak Alam / Noorhidayah Zaharuddin - Zaharuddin, Noorhidayah (2014)
Each of the students has their own preferable type of learning style. By knowing about their own learning style, it can help them to study better. The objective of this study is to identify the most preferable type of learning style among the first year and the fourth year pharmacy students at UiTM Puncak Alam and also to know its relationship with the student's performance. The questionnaire that had been used in this study was Leaming Style Questionnaire (LSQ) made by Peter Honey and Alan Mumford. It has been distributed to all the first year and the fourth year pharmacy students (n = 365) in UiTM Puncak Alam, Malaysia. This LSQ covered about four different types of learning styles which are theorist, pragmatist, activist and reflector. For this study, reflector was the most preferable type of learning styles among the respondents ( 4 7 .5% ), followed by pragmatist (14.8% ), theorist (I 0.5%) and activist (0.8%). Besides that, there were also some groups of student who had mixed type of learning style (26.5%). The preferred learning style which was reflector has no significant difference with all the demographic variables which include gender, age, current year of study and also current Grade Point Average (GPA) of the respondents except for highest education level. A variety method of teaching and learning activities has to be made to give a better learning process among pharmacy students that can be matched with their various kind of learning style.